Trigonometric splines in problems of constructing approximate solutions of the first boundary value problems for ordinary differential equations of second order - Денисюк, В.П.; Терещук, Г.М. (Proceedings of National Aviation University (archive), 2009)
The method of application of trigonometric splines is considered for the problems of construction of the approximate solution of the first boundary value problem for ordinary differential equations of the second orders with variable coefficients. By the method of collocations indefinite coefficients are determined.